2017
DOI: 10.1039/c7ra00150a
|View full text |Cite
|
Sign up to set email alerts
|

A robust duplex Cu/PDMS-coated mesh with superhydrophobic surface for applications in cleaning of spilled oil

Abstract: In this study, we created a robust and stable nanostructure coated on the surface of a stainless steel mesh via the electrodeposition of copper thin films and chemical modification with polydimethylsiloxane (PDMS) to enhance the mechanical durability of the stainless steel mesh surface with superhydrophobic performance. The obtained stainless steel mesh was tested by immersion in solutions of different pH values and abrasion cycling tests with sandpaper. The results showed that the coated stainless steel mesh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(31 reference statements)
0
7
0
1
Order By: Relevance
“…In general, the stability of the coating is more outstanding under the acidic condition. Compared with the work of Zhu et al, [ 30 ] in which the sample lost superhydrophobicity when the pH < 4, this superhydrophobic Ni coating is more tolerant in acidic environments.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…In general, the stability of the coating is more outstanding under the acidic condition. Compared with the work of Zhu et al, [ 30 ] in which the sample lost superhydrophobicity when the pH < 4, this superhydrophobic Ni coating is more tolerant in acidic environments.…”
Section: Resultsmentioning
confidence: 69%
“…As can be seen from Table 1, the i corr and E corr of stainless steel are 6.9116 × 10 −7 A cm −2 and −0.2245 V, respectively, and the i corr and E corr of the superhydrophobic sample are 1.5054 × 10 −8 A cm −2 and −0.1484 V, respectively. Usually, the sample with lower i corr and more positive E corr possesses a better corrosion resistance, [ 30 ] and all these data indicate that the superhydrophobic Ni coating improves the corrosion resistance of the sample. The Nyquist plots of the steel substrate and the superhydrophobic sample are shown in Figure 17b.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Water/oil mixtures treated with these materials should be further purified for daily human use. Recently, two-dimensional materials have attracted considerable attention to treat water/oil mixtures because of their energy-saving properties and economic advantages. ,, Various filtration films, with high flux values, have been prepared to remove oils from water with high flux. Metal meshes can be obtained by modifying the metal surfaces, which has been widely studied owing to its simple fabrication process. , Unfortunately, these materials need to be fixed within a filtration device; therefore, large-scale applications are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al . showed that when PDMS-coated copper mesh was subjected to 100 cycles of abrasion with the silicon carbide paper and load of 1 kg, the contact angle decreased from 156° to 139° due to the destruction of nanostructures 26 . Long et al .…”
Section: Introductionmentioning
confidence: 99%